2014
DOI: 10.1177/2167696814534417
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Adulthood

Abstract: Relatively little is known about the pathways youth with autism spectrum disorders (ASDs) take in the transition to adulthood in terms of employment and postsecondary education (PSE). Applying life course sequence analysis to a nationally representative sample of youth with ASDs (N ¼ 120), this study clustered various longitudinal sequences into three typical transition groups in the 6 years after high school exit: primarily focused on PSE (57.4%), continuously or increasingly disengaged (i.e., not employed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 25 publications
3
17
0
1
Order By: Relevance
“…Indeed a host of physical, interpersonal, educational, and other changes emerge throughout adolescence and into early adulthood. Although navigating these myriad transitions can be difficult for anyone, youth with disabilities often experience elevated challenges during this particular period of development (Forte et al 2011;Wei et al 2015). Among those students who may struggle most are youth with autism and youth with intellectual disability (ID).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed a host of physical, interpersonal, educational, and other changes emerge throughout adolescence and into early adulthood. Although navigating these myriad transitions can be difficult for anyone, youth with disabilities often experience elevated challenges during this particular period of development (Forte et al 2011;Wei et al 2015). Among those students who may struggle most are youth with autism and youth with intellectual disability (ID).…”
Section: Introductionmentioning
confidence: 99%
“…Second, Chiang et al (2013) found that social skills were significantly related to participation in postsecondary employment. Third, Wei, Wagner, Hudson, Yu, and Shattuck (2015) identified three primary pathways of postsecondary outcomes for students with ASD, including (1) primarily postsecondary education focused, (2) primarily employment focused, and (3) disengaged from both postsecondary education and employment; they further found that a brief measure of functional skills and conversational skills predicted which students were categorized as primarily postsecondary education focused, but these same skills did not differentiate between those in the other two groups. The current study aims to extend on these studies and the previous literature in several ways.…”
Section: Predictors Of Postsecondary Outcomes For Students With Asdmentioning
confidence: 97%
“…Additionally, the predictor variables used in this study (i.e., academic achievement and social skills) are based on data from instruments that have been developed to measure a broad range of academic and social skill proficiency levels and that have established technical adequacy. As opposed to use of categorical aca-demic and social skills variables in Chiang et al (2012), Chiang et al (2013), and Wei et al (2015), this allows for more specific examination of the levels of academic achievement and social skills that are more likely to result in successful postsecondary outcomes for the population of students in our study. Second, multiple postsecondary outcomes (i.e., education, employment, independent living, and overall success) will be examined in this study together, as it is important to explore the variety of postsecondary opportunities available to students with ASD.…”
Section: Predictors Of Postsecondary Outcomes For Students With Asdmentioning
confidence: 99%
“…Suboptimal learning environments will delay diverse learners' learning and preparedness to join the workforce eventually. About one-third of young adults with ASD are unemployed and not enrolled in postsecondary education; this rate is even greater among those with low socioeconomic status or among underrepresented minorities (Wei, Wagner, Hudson, Yu, & Shattuck, 2015). Considering students' young age and the prevalence of ASD, the impact of challenging learning environments is likely a significant cost to society.…”
Section: Introductionmentioning
confidence: 99%